2012
DOI: 10.1590/s0100-736x2012001100018
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of fibropapilloma associated herpesvirus of marine turtles in Rio Grande do Sul, Brazil

Abstract: is a benign tumoral disease that affects sea turtles, hampering movement, sight and feeding, ultimately leading to death. In Brazil, the disease was described for the ϐirst time in 1986. Research suggests the involvement of a herpesvirus in association with environmental and genetic factors as causal agents of FP. The objective of the present study was to detect and characterize this herpesvirus in sea turtles living in the coast of state Rio Grande do Sul (RS), Brazil. From October 2008 to July 2010, 14 turtl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…Most sequence variation was between regional ChHV5 strains rather than within a location, as expected based on previous phylogenetic analyses ( Herbst et al, 2004 ; Greenblatt et al, 2005a ; Greenblatt et al, 2005b ; Ene et al, 2005 ; Patrício et al, 2012 ; Rodenbusch et al, 2012 ; Alfaro-Núňez et al, 2014 ). A total of 1,001 fixed differences was observed between Hawaiian and Floridian samples across the 66 sequenced proteins.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Most sequence variation was between regional ChHV5 strains rather than within a location, as expected based on previous phylogenetic analyses ( Herbst et al, 2004 ; Greenblatt et al, 2005a ; Greenblatt et al, 2005b ; Ene et al, 2005 ; Patrício et al, 2012 ; Rodenbusch et al, 2012 ; Alfaro-Núňez et al, 2014 ). A total of 1,001 fixed differences was observed between Hawaiian and Floridian samples across the 66 sequenced proteins.…”
Section: Resultssupporting
confidence: 82%
“…Similar to previous studies, the majority of genomic variation was observed between geographic locations, with a total of 1,001 fixed differences detected between FL and HI variants. As suggested by previous molecular studies ( Quackenbush et al, 1998 ; Quackenbush et al, 2001 , Greenblatt et al, 2005a ; Greenblatt et al, 2005b ; Duarte et al, 2012 ; Patrício et al, 2012 ; Rodenbusch et al, 2012 ; Monezi et al, 2016 ), the divergent strains match predominantly regional movement patterns of sea turtle hosts, indicating that FP is geographically specific ( Herbst et al, 2004 ; Ene et al, 2005 ; Patrício et al, 2012 ; Jones et al, 2016 ; Ariel et al, 2017 ). Variability in rates of sequence divergence among ChHV5 genes was consistent with results noted for other alphaherpesviruses such as HHV-1, where the most divergent proteins were approximately 2.8% divergent ( Szpara et al, 2014 ).…”
Section: Discussionsupporting
confidence: 72%
“…The disease is transmissible in green turtles using cell-free tumor filtrates (21), and the disease-causing activity of these filtrates is abrogated by chloroform (22), suggesting an enveloped virus as an etiology. Molecular studies have consistently revealed herpesviral DNA in tumors from green turtles in Florida (23), Hawaii (24), and Brazil (25). More recently, herpesviral DNA has also been found in normal tissues from both tumored and nontumored green turtles in the Atlantic (26,27).…”
mentioning
confidence: 99%
“…On light microscopy, epidermal intranuclear inclusions (EII) have been seen in tumors that on electron microscopy contain herpesvirus-like particles (18). Additionally, herpesviral DNA is consistently detected in tumor tissues, but less commonly in nontumor tissues, from turtles from Hawaii (19), Florida (20), and Brazil (21). In 2012, the virus associated with FP, chelonid herpesvirus 5 (ChHV5), was designated the type for the newly erected genus Scutavirus of the subfamily Alphaherpesvirinae, family Herpesviridae (22).…”
mentioning
confidence: 99%